Potato yield and metabolic changes by use of biofertilizer containing L-glutamic acid - Röder, Cinthia; Mógor, Átila Francisco; Szilagyi-Zecchin, Vivian Jaskiw; Gemin, Luiz Gabriel; Mógor, Gilda (Comunicata Scientiae, 2018)
The identification of natural bioactive sources capable of enhancing yield gains on agriculture is a tool to promote sustainability. In this study, the effect of foliar applications of sugarcane molasses fermented by the bacteria Corynebacterium glutamicum, containing 30% (w/v) of the amino acid L-glutamic acid was tested on organically grown potato for two seasons. Four foliar applications at intervals of ten days were made using solutions with different concentrations of the fermented broth (0.2, 0.4, 0.6, 0.8 mL L-1). Total and commercial potato yield and biochemical alterations on leaves at 50 and 60 days after planting were determined. The applications of the fermented broth promoted yield gains and changes in chlorophylls, carotenoids, nitrate reductase enzyme (EC 1.6.6.1) activity, delaying the senescence and improving the free amino acid and soluble protein content of leaves. It was concluded that the fermented broth was able of improving potato yield by stimulating the nitrate reductase activity.